Hubungan Dukungan Suami dengan Keputusan Penggunaan Kontrasepsi Suntik 3 Bulan di TPMB Ny. Sofi Rufiah - Siska Panggabean; Tri Iriyani; Bagus Supriyadi (PT. PENERBIT TIGA MUTIARA, 2026)
Population growth that continues to increase has generated various social and health problems due to the imbalance between population size and the quality of human resources. This condition encourages the government to strengthen the implementation of the Family Planning Program as a strategic effort to control fertility among couples of reproductive age. The success of this program is influenced not only by access to health services but also by family support, particularly the husband’s support in decisions related to contraceptive use. This study aimed to analyze the relationship between husband’s support and the decision to use three-month injectable contraception among family planning acceptors. The research applied a quantitative approach with a correlational design and a cross-sectional research type. The population consisted of all family planning acceptors at TPMB Ny. Sofi Rufiah totaling 109 individuals, while the sample included 86 respondents selected through a random sampling technique. Data were collected using a structured questionnaire and analyzed statistically using the Chi-Square test through SPSS software. The results showed that the majority of respondents received support from their husbands, totaling 60 individuals (69.8%), while the use of three-month injectable contraception was reported by 49 respondents (57%). Statistical analysis indicated a significant relationship between husband’s support and the decision to use three-month injectable contraception with a significance value of p < 0.05, meaning the research hypothesis was accepted. These findings confirm that husband’s support is an important factor influencing women’s decisions in selecting contraceptive methods. The novelty of this study lies in emphasizing the role of husband’s support as a social determinant contributing to the successful use of three-month injectable contraception at the level of independent midwifery practice services. The results are expected to provide a foundation for strengthening family-based family planning education strategies.